Fat mobilization syndrome in beef cows due to poor adaptation to corn silage consumption (FAVE Sección Ciencias Veterinarias, 2025)
An outbreak of fat mobilization syndrome in breeding cows due to lack of adaptation to confinement is described in Salta, Argentina. The incidence was 8% and the lethality was 67%. Clinical signs included depression, unsteady gait, weakness, and eventual recumbency and death. Some animals in the final stages exhibited nervous signs such as blindness and walking in circles. Necropsy revealed mild jaundice in subcutaneous tissue, vascular endothelia, and organs in general, along with marked hepatomegaly, ocher coloration, and a greasy texture to the touch. Microscopically, severe hepatic lipidosis and retention of bile pigments were observed. Additionally, elevated levels of aspartate aminotransferase (AST=489±277), alkaline phosphatase (ALP 895±207 IU/L), and urea (48±13 mmol/L) were noted. Hepatic lipidosis is a well-known condition in dairy cows but is rarely described in breeding cows.
Keywords: hepatic lipidosis; beef cattle; maize